Contrarreforma do estado e a política de saúde mental: um estudo nos centros de atenção psicossocial infantojuvenis no estado da Paraíba - Silva, Segislane Moésia Pereira da (2021)
Public health and mental health institutions represent a fertile field marked by conflicts that have become a strong object of profitability for the capital. The Brazilian context in recent decades is marked by a counter-reform process in which the State itself is the main capitalist instrument for dismantling the advances achieved since the Sanitary and Psychiatric Reforms, proposed in the 1970s, which culminated in the consolidation of SUS in the face of a perspective of health as a universal right and the ideals of the anti-asylum struggle. This occurs, therefore, since the arrival of the neoliberal ideology on Brazilian soil, passing through the specificities of the governments of FHC, Lula, Dilma, and Temer. Currently, in Bolsonaro’s government, successive attempts to reduce the State and strengthen the private sector have been orchestrated, sometimes more clearly than others, depending on the particularities of each government. Considering this adverse scenario, the present study has as main objective the analysis and about the conditions to guarantee the effectiveness of the offer of the Mental Health Policy in the state of Paraíba regarding the care of CAPSi. The methodological path followed, in the search for understanding this problem, took place, at first, from a literature review, in which we recall how the arrival of the neoliberal ideology in the country was configured, and also how it was managed by the governments that have followed from the mid-1990s to the present, emphasizing their inflections in health and mental health policies. Through the theoretical framework of dialectical historical materialism, supported by qualitative research, as a way of valuing objective and subjective aspects, a study was carried out with 9 professionals working in 3 CAPSi in the state of Paraíba. The empirical material was produced based on questionnaires and semi-structured interviews conducted in the period between August and October of 2020. The analysis of the material was based on the Content Analysis technique proposed by Bardin, which resulted in two thematic units: 1) the objective conditions for the implementation of the mental health policy, which imply the financing, structuring and multidisciplinary teams of CAPSi; and 2) subjective conditions, which include the results of working conditions, the anguish and uncertainties arising from the context of the pandemic, the relationship between mental health and human rights and the identification of who these users and family members are in an intersectional way. This study enabled an understanding about the advances, limits and possibilities through the CAPSi towards the consolidation of the Psychiatric Reform with regard to the deinstitutionalization and overcoming the biomedical model. However, the results allowed us to identify numerous challenges and weaknesses that are present through the precariousness of these Centers, the working conditions of the technical team, professional relationships and institutions before mental health and human rights and, in particular, a perspective beyond the critical, sensitive look, towards who these children and adolescents are and also their family members and caregivers in our neoliberal, patriarchal and racist capitalist society.